RESIDU LEUKOSIT DALAM THROMBOCYTE CONCENTRATE - Nurmalia PS; Purwanto AP; Julia Julia (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Transfusion reactions in the thrombocyte concentrate (TC) manual is often associated with the storage time due to the release of cytokines by leukocytes during storage. The results showed the majority of transfusion reactions include fever/febrile non-haemolytic transfusion reaction (FNHTR). The quality control of blood components is necessary for the determination a component of blood in the bag already qualified for or not for transfusion. The aims of this study is to determine the residual leukocytes in the TC manual of Blood Donor Unit (UDD) at PMI Semarang with the shelf life of 3−5 days in compliance with the requirements of TC quality criteria of the European Union Council (EU).A Descriptive study is conducted at the Blood Donor Unit (UDD) PMI Semarang. The TC sample consist of 30 bags and manuals from the transfusion bag, which has been stored between 3−5 days. The examination of the residual leukocytes from the TC bag is carried out by manual microscopic method as well as the counting. The results obtained from the O blood group are 13 bags (43%) of TC, the B blood group seven (7) bags (33%), A blood group two bags (7%), and AB five (5) bags (17%). The range of the residual values of white blood cells in the TC manual is from 0 up to 0.0086×109/unit. According to the EU Council of leukocytes in the TC control value is <0.2×109/unit. The results of the residual leukocytes in the TC manual with the shelf life of 3−5 days are in accordance with the quality standards. This results indicates that the residual leukocytes in the TC manual UDD PMI Semarang in accordance with the EU quality standards.